EPIDEMIOLOGY OF CHRONIC HEART FAILURE IN IRKUTSK - E. B. Babanskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The purpose of a study was the prevalence of chronic heart failure under the dependence on the sex and. the age based on the example of the representative sample of adult population of Irkutsk. The prevalence of chronic heart insufficiency composed. 9,7 %.